Adaptability to High Temperature and Stay-Green Genotypes Associated With Variations in Antioxidant, Chlorophyll Metabolism, and γ-Aminobutyric Acid Accumulation in Creeping Bentgrass Species - Li, Zhou; Tang, Mingyan; Hassan, Muhammad Jawad; Zhang, Yan; Han, Liebao; Peng, Yan (Frontiers in Plant Science, 2021)
High temperature limits the cultivation and utilization of cool-season plants in many regions worldwide. Recently, extreme hot waves swept across the globe in summer, leading to enormous economic loss. The evaluation and identification of genotypic variation in thermotolerance within species are critical to breeding for environmental adaptation and also provide potential materials to explore thermo-resistant mechanism in plants. Forty-two accessions of creeping bentgrass (Agrostis stolonifera), which is a cool-season perennial grass for turf and ecological remediation, were collected from 15 different countries. Physiological traits, namely, chlorophyll (Chl) content, electrolyte leakage, photochemical efficiency, performance index on absorption basis, leaf relative water content, and osmotic potential were used to evaluate the heat tolerance of these materials in controlled growth chambers and field during summer. Stay-green and early-aging genotypes were selected to further reveal the potential mechanism of tolerance to senescence and heat damage associated with alterations in Chl metabolism, antioxidant and photosynthetic capacity, and endogenous γ-aminobutyric acid (GABA). Findings showed that there were significant genetic variations in physiological traits among 41 materials in response to high temperature stress. The 13M, PROVIDENCE, and LOFTS L-93 were the top three accessions with superior tolerance to heat and summer stress than other materials in terms of laboratory and field tests. In response to heat stress, the stay-green genotype PROVIDENCE exhibited significantly higher photochemical efficiency, net photosynthetic rate, transpiration rate, and water use efficiency than the heat-susceptible W6 6570. Delayed leaf senescence in relation to less Chl loss was detected in the PROVIDENCE associated with maintenance of significantly higher expression levels of Chl-anabolic genes (AsCHLH, AsPBGD, and AsPOR) and lower Chl-catabolic gene AsPPH under heat stress. Genetic attributes, such as better capacity to scavenge reactive oxygen species and higher endogenous GABA content could play positive roles in alleviating heat-induced senescence, oxidative damage, and metabolic disturbance in the PROVIDENCE.